2010
DOI: 10.1194/jlr.m004010
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipidomics of A2780 human ovarian carcinoma cells treated with synthetic retinoids

Abstract: This article is available online at http://www.jlr.org and ovarian cancers, neuroblastoma, lymphoma, and leukemia. Many pieces of evidence indicate a link between HPR's antitumor effect and the metabolism of sphingolipids in tumor cells. As for many other anticancer drugs, the studies in tumor cell lines indicated that apoptosis is the major cytotoxic mechanism for HPR [even if the toxic effect of HPR is likely very complex and at least in part due to nonapoptotic mechanisms ( 2, 3 )], and HPR-induced apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 30 publications
3
24
0
Order By: Relevance
“…De novo pathway is suspected to be the important mechanism in this type of cytotoxicity as evidenced by the increased levels of dhCer which is the intermediate product of this pathway. A similar observation was done in ovarian cancer cells treated with synthetic retinoids [129]. In this study, mass spectrometry analysis identified more than 30 species of sphingolipids, dhCer species being in particular, increased upon drug treatment,.…”
Section: Sphingolipids In the Perspective Of Chemo-therapeutic Responsesupporting
confidence: 56%
“…De novo pathway is suspected to be the important mechanism in this type of cytotoxicity as evidenced by the increased levels of dhCer which is the intermediate product of this pathway. A similar observation was done in ovarian cancer cells treated with synthetic retinoids [129]. In this study, mass spectrometry analysis identified more than 30 species of sphingolipids, dhCer species being in particular, increased upon drug treatment,.…”
Section: Sphingolipids In the Perspective Of Chemo-therapeutic Responsesupporting
confidence: 56%
“…Moreover, it has been demonstrated that dihydroceramide, rather than ceramide, accumulates in HPR-treated tumor cells, due to the inhibitory effect of this retinoid on dihydroceramide desaturase (22,24,37). Indeed we recently showed by electrospray ionization-MS analysis that dihydroceramide and not ceramide is increased upon treatment of A2780 cells with HPR (36). In addition, recent observations suggest that HPR cytotoxicity might at least in part due to the elevation of cellular sphinganine levels (24).…”
Section: Discussionmentioning
confidence: 98%
“…All together these data suggest that SK inhibition sensitized A2780/HPR cells to HPR-induced apoptosis. Because the antiproliferative and cytotoxic effect of HPR on A2780 cells is mediated by a HPR-induced elevation in cellular dihydroceramide levels (7,36), a higher SK activity in resistant cells might be responsible for a reduced capability to form dihydroceramide or ceramide (i.e. to a lower dihydroceramide/S1P ratio with respect to sensitive cells upon challenge with the drug).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blockade of Des1 produces an increase in dihydroceramides (dhCers), which have emerged as bioactive lipids and the target of several drugs ( 34 ), including fenretinide. Several studies have shown that cells respond to fenretinide treatment with a robust production of dhCers (35)(36)(37)(38)(39)(40)(41)(42)(43)(44), and that this increase induces autophagy ( 45,46 ). Furthermore, experimental evidence exists on the connection between resistance to fenretinide and increased S1P production ( 38,44 ) due to an increased SK activity and SK1 mRNA and protein levels ( 38 ).…”
Section: Des1 Enzyme Assaymentioning
confidence: 99%